Droplet Digital PCR (ddPCR) as a Novel Technology in Detecting CTNNB1 Mutations in Desmoid Fibromatosis. Issue 10 (14th November 2022) - Gandhi, Jatin; Kao, Erica; Wu, Yu; Mantilla, Jose G.; Ricciotti, Robert W.; Bandhlish, Anshu; Liu, Yajuan J.; Chen, Eleanor Y.
Abstract : Desmoid fibromatosis (DF) is a locally aggressive soft tissue neoplasm with frequent recurrences. DF is characterized by alterations in the Wnt/β-catenin pathway, with the majority showing sporadic mutations in CTNNB1, whereas others have germline mutations in APC . Immunohistochemical staining for β-catenin is often difficult to interpret and can be negative in up to 30% of cases. Prior studies have shown that some DFs lacking nuclear expression of β-catenin may carry activating CTNNB1 mutations. Droplet digital polymerase chain reaction (ddPCR) has been used effectively in detecting mutations in formalin-fixed, paraffin-embedded (FFPE) samples of various cancer types. In this study, we assess the diagnostic utility of ddPCR to detect CTNNB1 mutations in DF with β-catenin expression on immunohistochemistry (IHC), as well as in diagnostically challenging cases. Of the 28 DFs with nuclear β-catenin expression by IHC, 24 cases showed a CTNNB1 mutation by ddPCR using primers against the most common point mutations in CTNNB1 . The most frequent mutation was T41A (n=14; 50%), followed by S45F (n=8; 33%) and S45P (n=3;12%). We identified 8 additional (myo)fibroblastic lesions of uncertain classification, which were negative for nuclear β-catenin expression by IHC. We detected CTNNB1 mutations in 3 unknown lesions, including S45F (n=2) and S45P (n=1). ddPCR is a sensitive, rapid and cost-efficient methodology to detect common CTNNB1 mutations in DF, especially in diagnostically challenging cases.